Translation of Implied Sense as a Psycholinguistic Category - Kykot , Valeriy (East European Journal of Psycholinguistics, 2021)
The article aims to identify some implied sense markers in the poetic text to draw translators’ attention to their reproduction and scholars of translation on their analysis. The study of the creation, decoding, and translation of implied sense as a constituent of a poem’s macro-image structure in general, and with the untranslatable form of poetical implied sense based on Anglicism dispersion in the text of the American verse in particular, contributes to a better perception of the original poem and promotes finding ways of its adequate reconstruction in translation. This paper pioneers the idea that poetic implied sense as a psycholinguistic category is interpreted as making primary content of a poem and is considered a dominant image in poetic translation. Semantic context significance in poetic implied sense interpretation and translation are revealed. The presence of implied sense in poems is characterized by the text markers that help disclose it and direct translators. Poetical implied sense is determined as implied sense image functioning within a poem macro-image structure. Implied sense image decoding and rendering requires prior examination of the system of inner textual and extra-textual context relationships and psycholinguistic aspects of poetic discourse. Among the main tools applied in this study is the method of macro-analysis of a poetic work, which involves comparison of the original and translation at the level of autosemantic, synsemantic and subsemantic (implied sense) images and, in particular, text analysis to identify purely linguistic and psycholinguistic implied sense markers for its decoding and reproduction in translation, and factor analysis (principal components method) to determine the features of the semantics of the poetic original and translated texts. As a result of this research, it is discovered that signals-markers of the poetic implied sense are simultaneous actualization of the meanings of the same word and scattered inclusions of Anglicisms in American verse, which form an implied sense that is difficult to translate.